Influence of sex-role expectations on perceived work performance among employees in multinational corporations in Nigeria (2007)
The study, which adopted ex post facto research design, investigated the influence of sex role expectations on perceived work performance. A total of three hundred (309) employees were drawn from two multinational corporations in Nigeria. In all, two hundred and five (205) were males representing 66.6%, while the remaining one hundred and nine (109) were females representing 33.7% of the total participants. Their age ranged between 19-58 yrs with a mean age of 31.40 yrs (S.D = 7.03). Two hypotheses were tested in the course of the study. The result obtained revealed that there was a significant difference between employees high on male expected characteristics and those low on male expected characteristics on perceived work performance, (t(2, 294,) = 2.339 ;P<.05). However there was no significant differences between employees form Procter and Gamble and those from Fan Milk on perceived work performance, (t(2, 294,) = 1.517 ; P >.05). Based on the outcome of the results obtained, conclusions were drawn and recommendations made with emphasis on the importance of employees’ characteristics in selection and placement in organizations